MANAJEMEN KOMUNIKASI DAN NEGOSIASI PENDIDIKAN ISLAM MULTIKULTURAL - Elviani Sartika; H. Normudlim; Muslimah (STKIP Subang, 2026)
Multicultural Islamic education is an educational approach that places cultural, ethnic, linguistic, and social diversity as a reality that must be managed positively within the educational process. In this context, communication and negotiation are two crucial managerial instruments in building harmonious relationships among school members and maintaining organizational effectiveness. This study aims to analyze the concept of communication and negotiation management in multicultural Islamic education and to examine its implementation strategies within educational institutions. This research employs a library research method with a descriptive-analytical approach through the study of books, journals, and relevant literature. The findings indicate that communication management in multicultural Islamic education must be built upon openness, respect for differences, empathy, and participatory dialogue. Meanwhile, negotiation is needed as a mechanism for conflict resolution and achieving mutual understanding among educational stakeholders. Implementation strategies may be carried out through strengthening an inclusive organizational culture, improving leaders’ communication competence, and establishing internal mediation systems within educational institutions. Therefore, effectively managed communication and negotiation will support the creation of harmonious, adaptive, and high-quality Islamic educational institutions.